Toward a Multifaceted Model of Internet Access for Understanding Digital Divides: An Empirical Investigation - van Deursen, Alexander J. A. M.; van Dijk, Jan A. G. M. (The Information society, 2015)
In this investigation, a multifaceted model of Internet appropriation that encompasses four types of access-motivational, material, skills, and usage-is tested with a representative sample of the Dutch population. The analysis indicates that while the digital divide policies' focus has moved to skills and usage access, motivational and material access remain relevant since they are necessary through the entire process of Internet appropriation. Moreover, each type of access has its own ground of determination and they interact together to shape digital inequalities. Therefore, digital divide policies should address material, skills, and usage access simultaneously.